Pelatihan pembuatan batu bata di Kecamatan Ujung Bulu Kabupaten Bulukumba - Qadriathi Dg. Bau; Maryam H (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Community Partnership Program is one of thecommunity service programs which is problem solving,comprehensive, meaningful, complete and sustainable aimingfor diverse targets. Among the problems faced by thecommunity especially the small and medium enterprises is theutilization of technology. In particular, the problems which thebrick-making groups in Ujung Bulu Sub-district as PKMpartners have so far faced include: (1) insufficient knowledgein the efficient and effective process of brick making, (2)inadequate skills in accurate production of bricks, (3) lowcapability in massive production of bricks, 4) Less informationabout modern brick-making tools. The Community PartnershipProgram (PKM) for the brick-making groups in Ujung BuluSub-district aimed: (1) to increase knowledge in the efficientand effective process of brick making, (2) to improve skills inthe accurate production of bricks, (3) to promote capability inthe massive production of bricks (4) to increase the knowledgeand skills in the modern production of bricks. The methodsused for the presentation consist of lectures, discussion, andinteractive questions and answers, and demonstration for theapplied technology. The Community Partnership Program forthe brick-making groups in Ujung Bulu Sub-district hasresulted in: (1) sufficient knowledge in the efficient andeffective process of brick making, (2) adequate skills in theaccurate production of bricks, (3) decent capability in themassive production of bricks, (4) satisfactory knowledge andskills in the modern production of bricks.